Menganalisis Nilai-nilai Moral dari Karakter Desiree dalam Cerita Pendek (Désirée's Baby) oleh Kate Chopin - Intan Intan; Hening Putri Wayah Ratrie; Leni Dwi Astuti (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Etymologically, the word moral comes from the Latin mos, which means the customs that a person has towards the people around him. Meanwhile, the general meaning is the norms of life that are carried out in order to maintain the level of social order in life. Moral values ​​in general are points related to good and bad behavior that guide a person's life. Therefore, this research was created to describe the moral values ​​of